Lipidomic Analyses Reveal Specific Alterations of Phosphatidylcholine in Dystrophic Mdx Muscle - Valentine, William J.; Mostafa, Sherif A.; Tokuoka, Suzumi M.; Hamano, Fumie; Inagaki, Natsuko F.; Nordin, Joel Z.; Motohashi, Norio; Kita, Yoshihiro; Aoki, Yoshitsugu; Shimizu, Takao; Shindou, Hideo (Frontiers in Physiology, 2022)
In Duchenne muscular dystrophy (DMD), lack of dystrophin increases permeability of myofiber plasma membranes to ions and larger macromolecules, disrupting calcium signaling and leading to progressive muscle wasting. Although the biological origin and meaning are unclear, alterations of phosphatidylcholine (PC) are reported in affected skeletal muscles of DMD patients that may include higher levels of fatty acid (FA) 18:1 chains and lower levels of FA 18:2 chains, possibly reflected in relatively high levels of PC 34:1 (with 16:0_18:1 chain sets) and low levels of PC 34:2 (with 16:0_18:2 chain sets). Similar PC alterations have been reported to occur in the mdx mouse model of DMD. However, altered ratios of PC 34:1 to PC 34:2 have been variably reported, and we also observed that PC 34:2 levels were nearly equally elevated as PC 34:1 in the affected mdx muscles. Here, we aimed to more clearly define the mdx-specific PC alterations and other factors which may impact the PC 34:1 / PC 34:2 ratios. We performed comprehensive lipidomic analyses of PC and phosphatidylethanolamine (PE) in several muscles (extensor digitorum longus, gastrocnemius, and soleus) and determined the mdx-specific alterations. The alterations in PC 34:1 and PC 34:2 were closely monitored from neonate period to adult, and also in mice raised on several diets that varied in their fats. PC 34:1 was naturally high in neonate muscle and decreased until age 3-weeks (disease onset age), and thereafter remained low in WT muscles but was higher in regenerated mdx muscles. Among the muscle types, soleus showed a distinctive phospholipid pattern with early and diminished mdx alterations. Diet was a major factor to impact PC 34:1 / PC 34:2 ratios because mdx-specific alterations of PC 34:2 but not PC 34:1 were strictly dependent on diet. Our study identifies high PC 34:1 as a consistent biochemical feature of regenerated mdx-muscle and indicates nutritional approaches are also effective to modify the phospholipid compositions.